Beneath - Smith, Roland, 1951- (Scholastic Press, 2015)
Pat O'Toole has always idolized his older brother, Coop, right up until the day Coop ran away from their home just outside Washington, D.C. Now, a year later, he has received a package containing a digital voice recorder and a cryptic message from his brother, which will lead Pat on a strange and dangerous journey to the mysterious Community living beneath the streets of New York.